Keepers of the Vineyard and the Fence around the Torah: The Vineyard Metaphor in Rabbinic Literature - Teugels, Lieve M. (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2022)
Rabbinic texts apply the metaphor of the vineyard to the Torah as well as to Israel. Conceptual Metaphor Theory allows us to explain the parallel use of the vineyard metaphor for the two target domains, Israel and the Torah. The conceptual metaphor of the vineyard includes such aspects as the fence, the vines and the wine. The generic metaphor something precious is a cultivated piece of land enables us to include related conceptual fields, such as a field of wheat, or another cultivated piece of land. By means of the principle of the “creation of similarity,” the Torah and Israel are linked in the rabbinic cultural world, using the notion of preciousness, segulah. The metaphor of the vineyard not only reflects, but also induces the similarity: conceived as vineyards, Israel and the Torah become precious in the minds of the people using and hearing or reading the metaphorical texts.